Meningkatkan Partisipasi Belajar Peserta Didik melalui Media Crossword Puzzle pada Mata Pelajaran PPKn di SMP Negeri 1 Siantan - Eka Safitri; Amrazi Zakso; Shilmy Purnama; Sulistyarini Sulistyarini; Bistari Bistari (Departement of Mathematics Education, 2024)
This study aims to increase student learning participation by using crossword puzzle media in Civics subjects. The research method used in this research is a class action research method with a descriptive form. The research subjects in this study were class VIIIA students at Siantan 1 Public Middle School with a total sample of 28 people. Data collection techniques using observation, documentation, and interviews. Data collection instruments used were laptops, cellphones, pens, and books. The results of the data that have been collected are described by calculating the number of students and percentages. This research was conducted in 2 cycles, each cycle consisting of 1 meeting. The result of student participation in cycle 1 was 37% and in cycle 2 was 60%. Student learning participation has increased by using crossword puzzle media. Based on the results of the study it can be concluded that the use of crossword puzzle media in Civics subjects can increase the participation of class VIIIA students at SMP Negeri 1 Siantan.